Arquitetura e(m) Transição. A Circunstância no Ato de Projetar - Catarina Lima Vilarinho (2021)
In the first place, the concept of sustainable architecture, as one that respects not only the earth resources but also the place where it is born, presents itself as a possible solution for the reduction of the environmental footprint caused by the construction sector. However, the concept seems to have drowned itself in the technical concerns related to energy and resources usage that, being important factors, usually lead to an underestimation of the role of architecture in the promotion of a new spiritual and physical relationship (or the restitution of this relationship) between Man and Nature. Furthermore, it also seems to forget that "beauty is inherent to the definition and principles of sustainability"1 and that only with it, will architecture be able to create objects, buildings and new paradigms that will last while being respected by the people. Thus, and not forgetting that architecture is, in the first place, Man's shelter from the dangers and discomforts of Nature itself and, consequently, something inherently opposite to it, one tries to understand the principles of a conscious architecture, based on the concept of place established by Norberg-Schulz. It is an attempt to find a possible future for architecture based on values that go beyond those of the architect-artist-author. Taking continuity as a main value, skeptical of abrupt ruptures with the past and believing in History as a powerful learning tool, it is perceived that we are in a moment of transition and that it will happen through the rethinking of the interior-exterior transition itself, Man and Nature.